Pengaruh Religiusitas, Pengetahuan Perbankan, Pengetahuan Produk Perbankan, Pengetahuan Pelayanan Perbankan, Dan Pengetahuan Bagi Hasil Terhadap Preferensi Menggunakan Jasa Perbankan Syariah - Niken Nastiti; Arif Hartono; Ika Farida Ulfah (ASSET: Jurnal Manajemen dan Bisnis, 2020)
This research was conducted to test the Preference of Using PPTQ Al-Hasan Islamic Banking Services in Ponorogo Regency. The measurements used in this study use the variables Religiosity, Banking Knowledge, Banking Product Knowledge, Banking Service Knowledge, and Profit Sharing Knowledge. The data in this study are primary data with a data collection method using a questionnaire in the form of several structured statement items. The population in this study was students of PPTQ Al-Hasan in 2018 with 251 students. The sampling technique uses Non Probability Sampling: Purposive Sampling: and the number of respondents obtained with the results of 115 student students. Data analysis in this study used multiple linear regression analysis using the SPSS version program. 20. The results of this study indicate that the first hypothesis indicates that religiosity influences the preference for using Islamic banking services. The results of the second hypothesis testing indicate that banking knowledge influences the preferences of using Islamic banking services. The results of the third hypothesis testing indicate that the knowledge of banking products affects the preferences of using Islamic banking services. The fourth hypothesis testing results show that knowledge of banking services affects the preferences of using Islamic banking services. The results of testing the fifth hypothesis indicate that knowledge sharing results on preferences using sharia banking services. Simultaneous test results (F) indicate that religiosity, banking knowledge, banking product knowledge, banking service knowledge, and knowledge sharing results influence the preference for using Islamic banking services